China : Integration of National Product and Factor Markets, Economic Benefits and Policy Recommendations - World Bank (Washington, DC, 2012)
Lack of market integration has been a long-standing concern in China. The existing empirical evidence on the degree and trend in local protectionism and market fragmentation, has painted a mixed picture - some concluding to increasing fragmentation, others pointing at increasing integration. This report uses a comprehensive set of survey data, and a provincial data set to examine the extent and trends in market fragmentation. It finds mixed results across the three key markets in product, labor and capital: Since the early 1990s, the product market is increasingly integrating, with converging prices across the country, and increasing regional specialization. The survey data suggests strongly that regional protectionism declined significantly over the past 10 years. The labor market, while getting more integrated over the reform period, still shows significant fragmentation across regions and across sectors. The remains of the hukou system, the limited access migrants have to social services, and the highly uneven quality of public services reinforce labor market segmentations. The capital markets still show large misallocations in capital across industries, and across China's regions. More significantly, the empirical evidence indicates that the degree of capital market fragmentation has actually increased in the 1990s compared to the 1980s. As China is moving towards a Xiaokang Society, national market integration takes on increasing prominence. Indeed, the gains for China of better integration of goods and factor markets can be huge - much larger than the gains expected from the World Trade Organization (WTO) accession for which the country worked so hard. The report conducts policy simulations to estimate these gains. The report also estimates the economic gains from greater financial market integration. It conducts a simulation by changing the long standing urban bias policy through the movement of investment from cities to rural areas, while keeping the total amount investment constant. As a continental economy, it is time China starts its own determined effort to more rapidly integrate its markets, to maximize efficiency and growth, and ensure that the welfare gains get distributed more evenly across the nation.